Awareness and knowledge of medical emergency in dental clinic in Saudi Arabia: a cross sectional study - Sheikho, Maan Ahmed; Alyahya, Faisal Hamad; Alzahrani, Fahad Alhussain (International Journal Of Community Medicine And Public Health, 2018)
Background: In dentistry most of the medical emergency considered to be mild, and in some situation it can be very serious. The objective of our study is to assess knowledge and awareness of dental general practitioner, preparedness of dental clinic/team and the prevalence of most common medical emergencies encountered in dental clinics. Methods: This is a cross sectional study using self-administrated electronic questionnaire conducted on dental general practitioners (GPs) working in kingdom of Saudi Arabia during the months of January and February 2018 were recruited. Results: Less than half of the participants (47.3%) usually check vital signs before surgical extraction only and 42% before simple and surgical extraction and 8% before simple extraction only. Only 46.4% of the participants have experienced at least one medical emergency throughout their career. The most common medical emergency encountered is vasovagal syncope followed by hypoglycaemia and seizures, respectively. Majority of GPs have valid BLS and no one answered all question correctly. Conclusions: There are serious problems regarding the knowledge among dental GPs. Further studies needed to assess the education of medical emergency in schools of dentistry.